Adjudication for architects and engineers - Timpson, John (Thomas Telford, 1999)
Covers the aspects of construction adjudication, including the Housing, Grants, Construction and Regeneration Act 1996, Scheme for Construction Contracts, revisions to contracts and procedures, and others. This book is a guide to construction adjudication, for those involved with construction disputes, and for training adjudicators.